2018
DOI: 10.4103/ijmr.ijmr_1762_18
|View full text |Cite
|
Sign up to set email alerts
|

Country-specific nutrient requirements & recommended dietary allowances for Indians

Abstract: Nutrient requirements and recommended dietary allowances (RDAs) are set and revised periodically by the Indian Council of Medical Research. These are meant to guide the population and provide policy directions regarding nutrient requirements corresponding to a healthy population. This review article provides an overview of the current recommendations (RDA, 2010) and the challenges faced by the committee to contextualize RDA to the Indian scenario which has a background of double burden of malnutrition, diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…Our findings indicated that attitudes about one's own body weight influenced reported EI. 7 This may be true as more than 50% subjects in all age groups were either overweight or obese, as indicated by the Body mass indices of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated that attitudes about one's own body weight influenced reported EI. 7 This may be true as more than 50% subjects in all age groups were either overweight or obese, as indicated by the Body mass indices of the individuals.…”
Section: Discussionmentioning
confidence: 99%
“…41 In India "food insecurity" is defined as an average calorie intake of less than 2400 Kcal per capita per day based on direct calorie intake (DCI) method. 42 The NSSO conducts nationwide HCE surveys at regular intervals as part of its "rounds", with the duration of each round normally being a year. The surveys are conducted through interviews of a representative sample of households selected randomly through a suitable sampling design and covering almost the entire geographical area of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Mediterranean Equivalent Diet (MED). The Mediterranean diet plan from the Finnish Geriatric Intervention Study to Prevent Cognitive Impairment and Disability (FINGER) [13] trial was modified by experts primarily based on the Indian Council of Medical Research and National Institute of Nutrition Recommendations [14]. The diet regime comprised 20% of Daily Energy (DE) from proteins, 25% of DE from fat (<5% from saturated plus trans fatty acids, 0% from MUFA, and 20% from PUFA which includes 2.5-3g/day of omega-3 fatty acids), 55% of DE from carbohydrates (<10% from refined sugar), 30-35 g/day of dietary fibers, less than 5 g/day of salt, and no alcohol.…”
Section: Intervention Packagementioning
confidence: 99%